2017
DOI: 10.1007/s00259-017-3621-8
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of α7 nicotinic acetylcholine receptors: a comparative study of [18F]ASEM and [18F]DBT-10 in nonhuman primates, and further evaluation of [18F]ASEM in humans

Abstract: Purpose The α7 nicotinic acetylcholine receptor (nAChR) is implicated in many neuropsychiatric disorders, making it an important target for positron emission tomography (PET) imaging. The first aim of this work was to compare two α7 nAChRs PET radioligands, [18F]ASEM (3-(1,4-diazabicyclo[3.2.2]nonan-4-yl)-6-([18F]fluorodibenzo[b,d]thiophene 5,5-dioxide) and [18F]DBT-10 (7-(1,4-diazabicyclo[3.2.2]nonan-4-yl)-2-([18F]fluorodibenzo[b,d]thiophene 5,5-dioxide), in nonhuman primates. The second aim was to further as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 38 publications
2
36
1
Order By: Relevance
“…Due to the limited number of animals in this study, this observation merits further investigations. Our finding is however supported by PET studies in non-human primates with [ 18 F]ASEM and [ 18 F]DBT-10, where V T /f P was shown to be a more stable outcome measure than V T [44,45]. This has also been shown for radiotracers binding to other neurotransmitter receptors [75].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Due to the limited number of animals in this study, this observation merits further investigations. Our finding is however supported by PET studies in non-human primates with [ 18 F]ASEM and [ 18 F]DBT-10, where V T /f P was shown to be a more stable outcome measure than V T [44,45]. This has also been shown for radiotracers binding to other neurotransmitter receptors [75].…”
Section: Discussionsupporting
confidence: 78%
“…This phenomenon was most pronounced in the thalamus and least pronounced in the white matter and is evident from the TACs (Figure 4A), where the ratio between e.g., thalamus and cerebellum was lower at 240 min than at 90 min. This finding is in contrast with the non-human primate and human data, where V T was underestimated when reducing the PET data from 180 to 60 min [44]. Given that ASEM is an antagonist, it is unlikely that internalization of the receptor-ligand complex is an explanation for the decrease in V T .…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…18 F-FEOBV, 18 F-VAT, and 18 F-ASEM all show good peak brain activity, heterogeneous distribution in line with target distribution, and moderate to fast kinetics in most brain regions [65,73]. The exception is the slow kinetics of 18 F-FEOBV in basal ganglia structures requiring long scan durations or delayed scanning protocols for quantification in this region [65].…”
Section: Pharmacokinetic Properties Of Cholinergic Tracersmentioning
confidence: 87%
“…The brain uptake of 18 F-DBT-10 was inhibited by the administration of ASEM, in a dose-dependent manner (Hillmer et al 2016b). Hillmer et al directly compared the in vivo kinetic properties of 18 F-ASEM and 18 F-DBT-10 in identical rhesus monkeys and concluded that the two radiotracers were highly similar (Hillmer et al 2017).…”
Section: Imaging Probes For the α7 Subtypementioning
confidence: 99%